A Novel Keyword Ontology Generator Method Tested on “Digital Transformation in Higher Education” Topic - Cano, Laura Duque; Burgos, Daniel; Fernández, Carlos; Branch, John W.; Arango Serna, Martín Dario (Communications in Computer and Information Science, 2020)
The practice of using ontology to understand a field of study through the analysis of keywords was not found to have been documented, and a five-step method is therefore presented to generate ontologies of keywords: data selection and extraction, data unification strategy, keyword processing, weight and connection standardisation and final representation. Using the proposed method, an experimental evaluation was undertaken using as the field of study the digital transformation in universities and university institutions, generating a knowledge graph that enables the clear visualisation of the various connections among different topics in a chosen field of study. Finally, the effectiveness and the observed limitations are discussed while stressing that each researcher should perform a thorough analysis of those relationships, enabling to obtain useful information for teaching and learning processes, especially in higher education environments.
Ponencia de la conferencia "1st International Workshop on Higher Education Learning Methodologies and Technologies Online, HELMeTO 2019; Novedrate; Italy; 6 June 2019 through 7 June 2019"
Keywords: digital transformation; higher education; metadata; ontologies; Scopus(2)